The BAT case : putting tech support on the fast track - Lariviere, Martin A. (Martin Andre) (London : Kellogg School of Management, 2007)
The case explains the grown of Bruce Alfred Technologies and how the expansion of the company has put a strain on its customer service departments, lengthening the amount of time customers have to wait before speaking to a technician. The customer service department must consider whether to start a fast track service, whereby customers would pay to guarantee speaking to a technician in one minute or less.
Originally published in Larriviere, M. A. (2007). The BAT case: Putting tech support on the fast track. 5-207-250. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bruce Alfred Technologies; Public relations